Principles of modern chemistry - Oxtoby, David W.; Gillis, H.p.; Campion, Alan. (Australia : ThomSon, 2008)
Includes mathematically artistic representations of atomic and molecular orbitals that helps you derive information visually and see how the orbital equations translate into the orbitals' shapes.
Keywords: Chemistry. -- Manuels d'enseignement supérieur